External match loads of footballers with cerebral palsy: A comparison among sport classes - Yanci, J.; Castillo, D.; Iturricastill A.; Urbán, T.; Reina, R. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To determine and compare the external match load, according to sport class (FT), of footballers with cerebral palsy (CP) during the International Federation of CP Football World Championships Qualification Tournament. Methods: Forty-two international male footballers with CP participated in the data collection. The footballers with CP were classified according to their FT into 3 groups (ie, FT5/6, FT7, and FT8). External match load (ie, total distance covered, distance covered at different speeds, accelerations, decelerations, player load, peak metabolic power, and changes of directions) was collected for both halves during official matches with global positioning system devices. Results: Players with lower impairment (FT8) covered more distance (effect size=0.30-0.60) at high-intensity running (13.0-18.0 km/h) and sprinting (>18.0 km/h) and performed more (effect size=0.29-1.08) accelerations, decelerations, and changes of direction at high intensity in matches than did other players (ie, FT5/6 and FT7 groups). Conclusion: Because high-intensity actions are relevant to football performance and there are differences caused by players` impairments, the International Federation of CP Football classification protocols should include high-intensity actions during the technical assessment as part of the procedures for determining the sport class of football players with CP.